1998
DOI: 10.1007/s002280050512
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of intravenous methylprednisolone and oral prednisone in paediatric patients with inflammatory bowel disease during the acute phase and in remission

Abstract: In children with inflammatory bowel disease, the initial response to corticosteroid therapy was not influenced by the pharmacokinetics of prednisolone and methylprednisolone. In addition, the pharmacokinetics of prednisolone was not modified by the inflammatory syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 21 publications
0
7
1
Order By: Relevance
“…In our animal study, hyperglycemia was not observed. When MP is given in a small dose, the half-life varies from 3.8 to 7.2 h, which was sufficient in duration for our experiment to have the optimal effects from the drug (20). Clinically, arterial oxygenation during OLV remains an important parameter for the following reasons.…”
Section: Discussionmentioning
confidence: 99%
“…In our animal study, hyperglycemia was not observed. When MP is given in a small dose, the half-life varies from 3.8 to 7.2 h, which was sufficient in duration for our experiment to have the optimal effects from the drug (20). Clinically, arterial oxygenation during OLV remains an important parameter for the following reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Methylprednisolone pharmacokinetics is characterized by a very short half-life (about 2 hours) and although steroid binding to plasma protein is about 75%, the volume of distribution is very large (about 1.5 L/kg) [29]. These factors are the key of the negligible PLEX effect upon steroids biodisponibility [30, 31].…”
Section: Plasma Exchange Proceduresmentioning
confidence: 99%
“…We used MP at a concentration of 10 À6 M. This concentration is approximately equal to the plasma concentration of MP 1 h after the end of a 2-h intravenous administration of 2 mg/kg MP (Faure et al, 1998).…”
Section: Discussionmentioning
confidence: 99%